Analisis Investigasi Forensik dalam Mengungkap Penyebab Kematian pada Kasus Tenggelam - Meisy Fania Cantika Ketaren; Suandy Suandy (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Drowning is one of the leading causes of accidental death worldwide and remains a major challenge in forensic investigations due to the complexity of determining the exact cause and mechanism of death. This study aimed to analyze forensic investigation methods used to determine the cause of death in drowning cases. The research employed a qualitative descriptive literature review approach by analyzing scientific articles, forensic journals, and medical references related to drowning investigations. Data were collected through literature searches from Google Scholar, PubMed, and Portal Garuda using keywords related to forensic drowning investigations. The findings indicate that forensic investigation in drowning cases requires a comprehensive approach involving external examination, autopsy, laboratory examination, histopathology, diatom analysis, toxicology, and crime scene investigation. Typical forensic findings include foam cone, washerwoman’s hands, cutis anserina, emphysema aquosum, and the presence of foreign materials in the respiratory and digestive tracts. Diatom examination and histopathological analysis also play important roles in strengthening the diagnosis of drowning. The study concludes that an integrated forensic investigation based on scientific evidence is essential to accurately determine the cause and manner of death in drowning cases and to support medicolegal processes in Indonesia.